2016
DOI: 10.1111/tbj.12605
|View full text |Cite
|
Sign up to set email alerts
|

Impact of MammaPrint on Clinical Decision-Making in South African Patients with Early-Stage Breast Cancer

Abstract: The aim of the study was to evaluate the impact of MammaPrint on treatment decision-making in patients with breast cancer. Clinicopathologic information of all breast cancer patients referred for MammaPrint testing in South Africa was collected from 2007 until 2014. A total of 107 patients (109 tumors) with estrogen receptor/progesterone receptor positive and human epidermal growth factor receptor-2 negative tumors were selected with tumors ≥10 mm, or when 1-3 nodes were involved without extra-nodal extension.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 9 publications
(13 reference statements)
0
13
1
Order By: Relevance
“…Published data from South Africa on 109 ER/PR-positive, HER2-negative tumors showed a high risk-to-low risk ratio of 39% versus 61%, 16 whereas 68% of patients in the current series were high risk on MP, indicating that FISH positivity might predict a higher likelihood of a high-risk result but has poor PPV for HER2E.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…Published data from South Africa on 109 ER/PR-positive, HER2-negative tumors showed a high risk-to-low risk ratio of 39% versus 61%, 16 whereas 68% of patients in the current series were high risk on MP, indicating that FISH positivity might predict a higher likelihood of a high-risk result but has poor PPV for HER2E.…”
Section: Discussioncontrasting
confidence: 70%
“…On the basis of our findings in this study and the recent evidence from literature of the overestimation of HER2 positivity as determined by clinical guidelines, further evaluation of molecular subtyping in the work up of HER2-positive tumors should be considered, 33 including ER/PR-negative, cHER2-positive tumors < 10 mm. Institutional protocols, such as the MPA applied as a cost-saving strategy in the southern African context, 15 , 16 should be adapted to include patients with ER/PR-positive, cHER2-positive disease with limited nodal involvement to match the demographic characteristics of those reported in the MINDACT trial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Integration of these results into treatment decision may lead to a change in therapy in one of every two early-stage breast cancer patients treated in South Africa. 28 In the present study, the molecular subtype based on BP was used as an indicator of the expected response to therapy. The Luminal type of breast cancer is expected to respond to endocrine therapy, whereas the Basal subtype is inherently resistant to endocrine therapy.…”
Section: Discussionmentioning
confidence: 99%
“…ER, PR and HER2 status provide useful parameters for selection of patients eligible for transcriptional gene profiling, as evidenced in SA breast cancer patients referred for microarray analysis. Pohl et al [17] demonstrated a change in chemotherapy treatment in 52% of SA patients with early-stage breast cancer by using a newly developed microarray pre-screen algorithm to facilitate risk assessment beyond standard pathology and clinical prediction tools.…”
Section: Single-gene Testing Of Founder Mutations and Snpsmentioning
confidence: 99%